SURVIVABILITY IN METRO RING NETWORK USING OXADM - Mohammad Syuhaimi Ab-Rahman; Sahbudin Shaari (Universitas Gadjah Mada, 2007)
The optical cross add and drop multiplexing (OXADM) node described in this paper increases the capacity, flexibility and reliability of the trunk-line optical network used for data communication. It features two different bandwidths which operate in working and protection line in a ring configuration. The OXADM has the same features of the conventional OADM node but with more efficiency and reliability. The OXADM prototype system focuses on providing survivability through restoration against failures, such as cable/fiber cut in optical layer with ring topology. Two types of restoration scheme have been proposed to ensure data flow continuously by means of linear/ multiplex protection and ring protection. Comparison between OXADM and OADM restoration schemes is also described. The BER characteristics were measured at 2.5 Gbps (OC-48) and small degradation was observed, as confirmed by a comparison of these simulation results with those obtained from systems without restoration element. Restoration schemes in OXADM node are more reliable and efficient compare to conventional device due to internally routing mechanisms and no ‘drop and re-add function’ is needed to route the signal to alternative path or processed the signals in both electronic and optical domain as practice in conventional nodes today.